Visualization of attachment and colonization of pyrite surfaces by a novel species of Acidianus - Castro, Camila Andrea (2013)
In this work we have studied the attachment and colonization of pyrite surfaces by the recently isolated thermophilic archaeon Candidatus Acidianus copahuensis (from the geothermal Caviahue-Copahue system, Argentina). Cells pregrown with sulfur, iron(II) or pyrite were tested. In order to characterize the EPS glycoconjugates of this strain, fluorescent lectins were used. Concanavalin A (ConA) gave the best signal and was selected for further studies. Coupons and grains of pyrite were treated with DAPI (to stain attached cells) and TRITC-ConA (to stain polysaccharides from EPS). Pyrite surfaces were imaged by epifluorescence (EFM) and confocal laser microscopy (CLSM). Initial cell attachment to pyrite grains was estimated to be 26%, 35% and 43% when cells were pregrown with sulfur, iron(II) and pyrite as electron donors, respectively. It was observed that the cell adhesion correlated with an increase of EPS production; both processes were favoured when cells were pregrown with pyrite or iron(II). Also the effect of inorganic phosphate (Pi) starvation in the attachment of Acidianus was studied in similar tests using a base medium without Pi. An increase of cell attachment under Pi starvation conditions was detectable.